PWE-434 Evaluation of the impact of the learning context on the acquisition of complex professional skills through simulation based training courses. (22nd June 2015) - Keane, MG; Allain, TJ; Mwandumba, HC; O'Toole, PA; Gill, D; Gordon, MA
Abstract : Introduction: Rates of upper gastrointestinal pathology requiring diagnostic and therapeutic intervention in Southern Malawi are high, resources and endoscopy services are limited, and there are very few independently practicing endoscopists. Endoscopy is recognised to be a complex cognitive and technical skill that requires a dedicated period of training to achieve proficiency. An endoscopy-training programme developed for UK trainees that includes simulation, was introduced to Malawi in 2009. This study explores the commonalities and differences in the way simulation training was experienced and made use of by endoscopy trainees in both countries. It also explores what modifications are needed to make current courses maximally beneficial in a resource limited environment. Method: Trainees and trainers from the UK and Malawi were invited to participate in semi-structured interviews. During the interview trainees were asked to describe the structure of their endoscopy training, experiences of simulation training and outline perceived benefits and drawbacks of their programme. Trainers were asked about their views on endoscopy training, experiences as course faculty and any modifications they felt were necessary to current training programmes to make them maximally beneficial in each country. Interview data was transcribed in full and analysed using a thematic analysis approach. Results: 17 people participated in the study: 4 trainers (3 with experience of training in Europe and Malawi), 2 Endoscopy sisters and 11 trainees (4 from Malawi and 7 from the UK – two of the Malawi trainees subsequently became local trainers). Although there were considerable differences in the learning environment between the UK and Malawi, trainees recognised simulation based endoscopy-training courses as an important opportunity for intensive skill based training, which supplemented their on-going departmental endoscopy training. Factors that improved the trainee learning experience during the courses included: being taught by skilled trainers; trainees identifying a need or clinical application for their endoscopy training; and course design, specifically having access to simulation models prior to being exposed to live cases. Suggested modifications to the training programme in Malawi included; implementing robust candidate selection to prevent "drop-out" from the training programme and improving local equipment. Conclusion: UK designed simulation based endoscopy-training courses were well received by Malawian trainees and needed only minor modification to be applicable and beneficial in their new environment. Disclosure of interest: None Declared.